Ethiopia climate-smart agriculture roadmap - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Roadmap is developed based on context analysis of Ethiopian agriculture, aims to strengthen role of Ministry of Agriculture in addressing vulnerabilities facing agriculture sector under climate change by institutionalizing CSA.